2014
DOI: 10.1515/jbcr-2015-0125
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Angiomyolipoma: A Case Report, Differential Diagnosis with Pecoma and Review of the Literature

Abstract: Angiomyolipomas are benign mesenchymal neoplasms, presenting with a variable mixture of adipose tissue, smooth muscle and vascular component. Although they are typically found in the kidneys, many cases of extrarenal angiomyolipomas have been reported. They are extremely rarely present in the uterus. We describe a case of a 56-year-old woman, operated on for leiomyoma. Total laparohysterectomy and bilateral adnexectomy was performed. After histological and immunohistochemical examination, the final diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…1,2 Totev et al have suggested that an epithelioid AML is a kind of PEComa and hence, advised to do melanocytic markers in all uterine mesenchymal tumors with epithelioid appearance. 9,10 Surgical resection is the mainstay of treatment for uterine AML. Most cases are treated by total abdominal hysterectomy with or without salphingooophorectomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Totev et al have suggested that an epithelioid AML is a kind of PEComa and hence, advised to do melanocytic markers in all uterine mesenchymal tumors with epithelioid appearance. 9,10 Surgical resection is the mainstay of treatment for uterine AML. Most cases are treated by total abdominal hysterectomy with or without salphingooophorectomy.…”
Section: Discussionmentioning
confidence: 99%